Purification, Characterization, and Bioactivities of Polyphenols from Platycladus orientalis (L.) Franco. Issue 3 (19th February 2019) - Ren, Jiaoyan; Liao, Linfeng; Shang, Shuaiming; Zheng, Yamei; Sha, Wanqian; Yuan, Erdong
Abstract : Abstract: The polyphenols (PF) from Platycladus Orientalis (L.) Franco leaves were purified by using 10 different macroporous adsorption resins. HPD‐722 resin showed the best adsorption and desorption capacities. The static and dynamic adsorption and desorption of PF on HPD‐722 resin were studied and the total polyphenols were separated into two fractions, PF‐A and PF‐B. PF‐A and PF‐B demonstrated similar scavenging activity of free radical (DPPH, ABTS, hydroxyl radical, superoxide anion). The scavenging activity of PF‐A and PF‐B on hydroxyl radical and superoxide anion radical reached the equal levels of vitamin C and gallic acid. The IC50 value of PF‐A for hydroxyl radical scavenging activity and superoxide anion radical scavenging activity were 0.50 and 0.56 mg/mL, while those of PF‐B were 0.61 and 0.64 mg/mL. PF‐A and PF‐B could reduce the overproduction of inflammatory cytokines (TNF‐α, Pro‐IL‐1β, and IL‐6) induced by lipopolysaccharide and their protein expression in THP‐1 cells. PF‐B exhibited better anti‐inflammatory effect than PF‐A in the dosage range of 1.0–4.0 µg/mL. Structural identification of PF‐A and PF‐B were conducted by HPLC‐MS/MS. Ten polyphenol compounds were identified in PF‐A and PF‐B, respectively, by HPLC‐MS/MS, including quercetin, apigenin, myricetin, and so on. Molecular docking studies indicated that apigenin, myricetin, luteolin, kaempferol, and quercetin effectively inhibit xanthine oxidase by forming hydrogen bonds with the amino acid residues and binding to the active site of the enzyme. The results might supply useful information for better understanding the chemical structure, antioxidant, and anti‐inflammatory activities of Platycladuso (L.) Franco leaves polyphenols. Practical Application: This study demonstrated that polyphenols from P. orientalis (L.) Franco leaves have the potential applications as functional food ingredient for the prevention and treatment of gout and inflammation, hyperuricemia and gout.